The Strategic Role of Bystander Intervention and Digital Media in Preventing Sexual Violence - Sharon Angelita Halim; Intan Primadini (Communicatus: Jurnal Ilmu komunikasi, 2025)
This study aims to explore the strategic role of bystander intervention and the utilization of digital media in the prevention of sexual violence. Employing a descriptive qualitative approach with Robert E. Stake’s case study method, the research involved five female participants with experience as responsive bystanders. It uncovers how female responsive bystanders utilize digital media not only to respond to sexual violence but also to build solidarity, disseminate public awareness, and document survivor experiences as part of prevention efforts. The findings indicate that although participants do not always follow every stage of the Bystander Intervention Process, they consistently demonstrate active engagement in preventing or responding to sexual violence through intervention strategies such as direct, distract, and delegate. Some factors, such as emotional proximity, personal experience, and perceived risks, influence the intervention undertaken. Significant challenges for bystanders include situational ambiguity, past trauma, and prevailing social norms. Conversely, social media is recognized as a strategic tool for fostering collective digital support, voicing survivor experiences, and providing valid forensic evidence. The pattern of micromobilization within digital movements strengthens public awareness regarding sexual violence issues. This study reinforces the complementary roles of bystanders and digital media in creating safe spaces and progressive social change.